2012
DOI: 10.1021/np300149y
|View full text |Cite
|
Sign up to set email alerts
|

Eunicidiol, an Anti-inflammatory Dilophol Diterpene from Eunicea fusca

Abstract: A new dilophol diterpene, eunicidiol (1), has been isolated from the crude extract of Eunicea fusca, a gorgonian coral collected from Hillsboro Ledge, Florida. This compound was purified, along with fuscol (2) and eunicol (3), using a combination of normal- and reversed-phase chromatography methods. The structure of eunicidiol (1) was elucidated by 1D and 2D NMR spectroscopic analysis, and the absolute configuration was assigned using Mosher's method. The anti-inflammatory activity of 1-3 was evaluated by meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
(13 reference statements)
0
8
0
1
Order By: Relevance
“…776 Eunicidiol 1009 and known related diterpenes eunicol 777 and fuscol 777 were identied as potent topical anti-inammatory metabolites of Eunicea fusca (Hillsboro Ledge, Florida). 778 Extracts of Lobophytum pauciorum (Taketomijima Is., Okinawa) 779 provided cyclolobatriene 1010 and the related metabolites lobatriene, 780 eunicol 777 and fuscol. 777 A low temperature (7 C) NMR spectrum of 1010 identied three conformational isomers, while heating to 70 C induced a thermal Cope rearrangement to lobatriene (identical by NMR and sign of [a]).…”
Section: Cnidariansmentioning
confidence: 99%
“…776 Eunicidiol 1009 and known related diterpenes eunicol 777 and fuscol 777 were identied as potent topical anti-inammatory metabolites of Eunicea fusca (Hillsboro Ledge, Florida). 778 Extracts of Lobophytum pauciorum (Taketomijima Is., Okinawa) 779 provided cyclolobatriene 1010 and the related metabolites lobatriene, 780 eunicol 777 and fuscol. 777 A low temperature (7 C) NMR spectrum of 1010 identied three conformational isomers, while heating to 70 C induced a thermal Cope rearrangement to lobatriene (identical by NMR and sign of [a]).…”
Section: Cnidariansmentioning
confidence: 99%
“…As shown in Table 2, and in contrast to the 20 marine compounds ( 115 – 134 ) with described anti-inflammatory mechanisms of action, for marine compounds ( 135 – 157 ), only anti-inflammatory activity, namely IC 50 , was reported, but the molecular mechanism of action remained undetermined: A. polyacanthus steroids ( 135 , 136 ) [137]; barettin ( 137 ) [138]; briarenolide F ( 138 ) [139]; diketopiperazine ( 139 ) [140]; 6- epi -cladieunicellin F ( 140 ) [141]; crassarosteroside A ( 141 ) [142]; cystodione A ( 142 ) [143]; densanins A and B ( 143 , 144 ) [144]; dissesterol ( 145 ) [145]; echinohalimane A ( 146 ) [146]; eunicidiol ( 147 ) [147]; flexibilisolide C ( 148 ) [148]; flexibilisquinone ( 149 ) [149]; lobocrassin F ( 150 ) [150]; perthamide J ( 151 ) [151]; pseudoalteromone A ( 152 ) [152]; sarcocrassocolide M ( 153 ) [153]; sclerosteroids K and M ( 154 , 155 ) [154]; seco-briarellinone ( 156 ) [155]; and sinularioside ( 157 ) [156]. …”
Section: Marine Compounds With Antidiabetic and Anti-inflammatory mentioning
confidence: 99%
“…In 2012, eunicidiol ( 223 ) , a new dilophol‐type diterpenoid possessed a cyclodecane ring as well as an C 8 side chain, was obtained from Florida specimen of the gorgonian coral E. fusca . The authors proposed the biosynthetic pathway shown in Scheme .…”
Section: Diterpenoidsmentioning
confidence: 99%